2017
DOI: 10.3390/rs9111089
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Sea Surface Temperature Variability from UAV and Satellite Measurements

Abstract: Earlier studies of spatial variability in sea surface temperature (SST) using ship-based radiometric data suggested that variability at scales smaller than 1 km is significant and affects the perceived uncertainty of satellite-derived SSTs. Here, we compare data from the Ball Experimental Sea Surface Temperature (BESST) thermal infrared radiometer flown over the Arctic Ocean against coincident Moderate Resolution Imaging Spectroradiometer (MODIS) measurements to assess the spatial variability of skin SSTs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
6
20
0
1
Order By: Relevance
“…Spectral slopes of k -2 to k -3 are consistent with the kinetic energy spectra for mesoscale to submesoscale variability [15,19]. [15] compared spectral slopes from MODIS Terra and Aqua, as well as an Unmanned Surface Vehicle (Ball Experimental Infrared Radiometer). They found spectral slopes of k -2 for wavelengths between 10 m and 100 km, thus encompassing primarily submesoscale variability.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Spectral slopes of k -2 to k -3 are consistent with the kinetic energy spectra for mesoscale to submesoscale variability [15,19]. [15] compared spectral slopes from MODIS Terra and Aqua, as well as an Unmanned Surface Vehicle (Ball Experimental Infrared Radiometer). They found spectral slopes of k -2 for wavelengths between 10 m and 100 km, thus encompassing primarily submesoscale variability.…”
Section: Discussionsupporting
confidence: 52%
“…Spectral slopes were calculated for the SST and SSS spectra (see Table 4). Overlaid on Figures 7 and 8 (as a reference) is the spectral slope of k -2 , which is used as a reference as it is commonly associated with power spectra resolving the mesoscale variability [15]. Table 4 summarizes the spectral slopes, based on the above spectra of the different SST and SSS products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have examined subpixel‐scale surface temperature variability by using airborne systems. However, due to the challenges intrinsic to thermal image registration over water (Rahaghi et al, ) or instrumental restrictions, they only reported along‐track point (Mahrt & Khelif, ) or area‐averaged (Castro et al, ) measurements. These studies observed skin temperature variations of >1 °C within ~1‐km distance, which can affect the area‐averaged surface heat flux calculation.…”
Section: Introductionmentioning
confidence: 99%
“…structures can be brought to bear on the inversion problem as a further constraint. Sub-mesoscale fluctuations in SST fields can exist (Castro et al, 2017), but most oceanic near-surface wind speed variability is synoptically forced and thus spatial decorrelation lengths are significant. Wind retrievals can also benefit from accounting for spatial correlations for ambiguity removal (Vogelzang and Stoffelen, 2018;Lin et al, 2016).…”
mentioning
confidence: 99%